The Influence of Citizenship Education Learning Using the Sociodrama Method on Students' Social Concern - Lestari, Puji; Okon, Cecilia (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: This research aims to determine the effect of Civic Education (Citizenship Education) learning using the sociodrama method on the social awareness of class V students at Selang State Elementary School, Wonosari District, Gunungkidul Regency. Methodology: This research is a quasi-experimental research. The research design is Nonequivalent Control Group Design. The subjects of this research were class V students at Selang State Elementary School, totaling 57 students and consisting of two classes. Data collection techniques used in research include scales, interviews, observation and documentation. Test the validity of the instrument using the help of Expert Judgment. Test data analysis requirements using normality and homogeneity tests. Hypothesis testing uses the t test with a significance level of 5% . Main Findings: The main finding of this research is that Civics learning using the sociodrama method has a significant positive impact on the social awareness of fifth grade students at Selang State Elementary School in the 2012/2013 academic year. This is shown by the t test in the post test of the experimental-control group which shows a significant difference between the post test of the experimental and control groups after being given treatment Novelty/Originality of this study: The novelty of this research is the use of a new learning method, namely the sociodrama learning method. Civics learning using the sociodrama method has a significant positive impact on the social awareness of class V students at Selang State Elementary School. This was shown by the t test on the post test of the experimental-control group which showed a significant difference between the post test of the experimental and control groups after being given the treatment.